Bio-Chemical Management of Grey Blight of Mustard Through Selected Botanicals and Chemicals - Kabir, MH; Ara, YA; Uddin, AJM Moin; Islam, MA; Hossain, MB (SAARC Journal of Agriculture, 2022)
Grey Blight of Mustard caused by Alternaria sp. is one of the most important diseases of oil producing crop of Bangladesh causing heavy yield loss which is approximately 30-40%. In this study the effectiveness of selected botanicals, chemicals and their combined effects were assessed to manage this disease. Fourteen treatments including control were evaluated viz. T1= Control, T2= Trichoderma harzianum suspension, T3= Autostin 50 WDG, T4= Rovral 50 WP, T5= Dithane M- 45, T6= Amistar Top 325 SC, T7= Neem leaf extract, T8= Allamanda leaf extract, T9 = Lantana leaf extract, T10= Datura leaf extract, T11= Neem leaf extract+ Rovral, T12= Datura leaf extract + Amistar Top, T13= Lantana leaf extract + Dithane M- 45 and T14= Allamanda leaf extract + Autostin. Among the chemicals, the lowest disease incidence (%), disease severity (%), disease severity index (%) and pod infection (%) was found in T5 treatment (Dithane M-45) which was 55.91%, 22.09%, 32.16% and 6.72%, respectively, at 70 and 75 DAS, respectively. While among the botanicals, the lowest disease incidence (%), disease severity (%), disease severity index (%) and pod infection (%) was found in T9 treatment (Lantana leaf extract) which was 65.05%, 28.89%, 37.96% and 13.79%, respectively, at 70 and 75 DAS, respectively. In case of combined treatments, the lowest disease incidence (%), disease severity (%), disease severity index (%) and pod infection (%) was found in T13 treatment (Lantana leaf extract + Dithane M-45) which was 59.14%, 26.32%, 38.20% and 12.30%, respectively, at 70 and 75 DAS respectively. While the highest disease incidence (%), disease severity (%), disease severity index (%) and pod infection (%) was found in T1 treatment (Control) which was 79.20%, 37.54%, 67.38% and 34.63%, respectively, 70 and 75 DAS, respectively. Among the treatments yield and yield attributers were found better in T5 (Dithane M-45), T9 (Lantana leaf extract) and T13 (Lantana leaf extract + Dithane M-45). From the results on different parameters studied, the treatment Lantana leaf extract (T9), Dithane M-45 (T5) and their combined treatment (T13) can be used for management of grey blight mustard after few field trialing in consecutive year. SAARC J. Agric., 19(2): 219-232 (2021)